Faces of communion : a systematic approach from the theology of Yves M.-J. Congar (Teología, 2019)
The author makes a re-reading of Yves M.-J. Congar’s thought on ecclesial communion by proposing a new systematization around the idea of “faces”. This allows one to go through the French theologian’s fundamental themes: communion, as the bond with the Trinitarian mystery (theological face), as internal links to the People of God (ecclesiological face), as dialogue and communion with the world (pastoral face), as continuity and novelty in ecclesial tradition (historic/traditional face) and as a search for complete unity with other christians (ecumenical face). This text tries to recover the valuable contribution of one of the active protagonists of Vatican II, in order to look with hope to the challenges of post-conciliar ecclesiology.
Keywords: Yves M.-J. Congar; Communion; Church; Vatican Council II